Nick Land's Accelerationism as Writing: between Deleuze and Bataille - Gómez Solano, Paulo (2025)
The traditional caricature of accelerationism has understood it as a heretical strand of Marxism which, related with a Deleuze-Guattarian theory of flows, holds that the only way to achieve a post-capitalist society is by intensifying capitalist relations of production. This article argues, on the contrary, that accelerationism, since its formulation, has been defined as a process or "practice of immanence" inseparable from its way of writing. This approach allows us to show the distance and resignification of concepts that Nick Land took place respect to the series Capitalism and Schizophrenia, as well as the high resonance of his writing with Bataille's gospels —as Land himself referred to his work—.